Investigations on Trimming Strategy and Unsteady Aerodynamic Characteristics of Tiltrotor in Conversion Procedure - Zhao, Guoqing; Cui, Zhuangzhuang; Zhao, Qijun; Chen, Xi; Li, Peng (Aerospace, 2024)
Numerical simulations were conducted to analyze the unsteady aerodynamic characteristics of a tiltrotor aircraft with different conversion strategies. Firstly, the CFD method was established by taking the interaction between the rotor and wing into account, as well as the body-fitted grid of the tiltrotor. Then, the trimming approach of the rotor and wing was developed to ensure longitudinal balance of the aircraft, and the method for determining the conversion corridor of the tiltrotor aircraft was proposed by considering the limitations imposed by wing stall and the required power of the rotor. Finally, the aerodynamic characteristics of the rotor and wing during the continuous conversion process were investigated, considering various tilting angular velocities and horizontal accelerations of the tiltrotor. The numerical results indicated that a smaller acceleration can enhance the efficiency of the tiltrotor. However, this would increase the complexity of trimming the fuselage attitude angle. It was also found that excessive acceleration could exceed the required power limit of the tiltrotor, rendering the conversion strategy infeasible.